1997
DOI: 10.2176/nmc.37.336
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Treatment of Iatrogenic Dissection of the Internal Carotid Artery with the Palmaz-Schatz Stent —Case Report—

Abstract: He has experienced no cerebral ischemic events since the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…8 However, acute treatment of CAD has already been described in seven patients. [9][10][11][12][13] In five instances stents were placed at the time of an iatrogenic dissection. [9][10][11] The two remaining cases were acutely treated in the setting of worsening and fluctuating neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 However, acute treatment of CAD has already been described in seven patients. [9][10][11][12][13] In five instances stents were placed at the time of an iatrogenic dissection. [9][10][11] The two remaining cases were acutely treated in the setting of worsening and fluctuating neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] In five instances stents were placed at the time of an iatrogenic dissection. [9][10][11] The two remaining cases were acutely treated in the setting of worsening and fluctuating neurological symptoms. 12,13 As for the cases described in this study, there was no morbidity nor mortality after the procedure and all authors reported clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…8,15,24,25 The early success of stent placement for abdominal aortic aneurysms and other P. Jabbour, C. Koebbe, and R. Rosenwasser peripheral lesions like traumatic extracranial carotid artery dissections and pseudoaneurysms has been a valuable contribution to the development of intracranial stent delivery techniques. 4,14,16,27,32,35,37 There are still some difficulties and complications ranging from technical pitfalls to thromboembolic events that are encountered with the use of intracranial stents. …”
Section: Discussionmentioning
confidence: 99%
“…19,57 In recent years, stenting has been increasingly used to treat traumatic dissections and pseudoaneurysms of the cervical carotid and vertebral arteries. 20,[58][59][60][61][62][63][64][65][66] This has proven to be a particularly useful strategy in patients with symptomatic dissections in whom anticoagulation may be contraindicated due to concurrent injuries, patients who become symptomatic despite adequate anticoagulation, and patients with pseudoaneurysms which are unlikely to heal even with anticoagulation. 15 At our institutions, patients are initially treated with heparin or antiplatelet therapy where feasible.…”
Section: Treatmentmentioning
confidence: 99%